FISH MUCUS: A NEGLECTED RESERVOIR FOR ANTIMICROBIAL PEPTIDES - Hedmon, Okella (Asian Journal of Pharmaceutical Research and Development, 2018)
Antimicrobial resistance has posed a great global burden, with the fear that by 2050 it would have killed more people than cancer if nothing much is done about it. Alongside several attempts in place, zoo-therapy is becoming one of important remedies in the modern society, with hope for solution believed to be hidden in nature. In this study, the authors present a review of journal articles and reports obtained through key word search of several literature databases on recent developments in the battle against the antimicrobial resistance using fish derived antimicrobial peptides. The findings indicate despite some limitations of these antimicrobial peptides, their very broad spectrum activity against pathogens keeps them among promising antibiotics as far as the battle against multidrug resistance is concerned. Much as various methods to study antimicrobial peptides do exist, fish mucus remains less explored. The study recommends aquatic habitat exploration in search for novel bacterial antimicrobial peptides.